2017
DOI: 10.5812/jjm.58032
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Distribution of blaOXA-23 Gene Among Acinetobacter baumannii Isolated from Intensive Care Unit Patients in Tehran; Pulsed-Field Gel Electrophoresis Analysis

Abstract: Background: Despite a relatively low virulence of Acinetobacter baumannii isolates, emerging multidrug-resistant (MDR) strains to pose a formidable threat to patients, particularly in ill patients in intensive care unit (ICU). Objectives: The aim of the present study was to determine the genetic relatedness and antimicrobial susceptibility patterns in the endemic clones of A. baumannii isolated from patients in the ICU. Methods: Fifty-five non-repetitive A. baumannii isolates were examined for antimicrobial su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…In this study, bla OXA-23 , bla VIM , and bla NDM were detected This study concluded that highly resistant bla OXA-23 gene-harboring endemic clones of A. baumannii were disseminated in the ICUs of two studied hospitals (35). The bla VIM is another β-lactamases encoding genes with a frequency of 69.23% in this study.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In this study, bla OXA-23 , bla VIM , and bla NDM were detected This study concluded that highly resistant bla OXA-23 gene-harboring endemic clones of A. baumannii were disseminated in the ICUs of two studied hospitals (35). The bla VIM is another β-lactamases encoding genes with a frequency of 69.23% in this study.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, the imipenem MIC 90 for all isolates was (35). Unfortunately, in this study, 7.69% of the isolates were resistance to all tested antibiotics, which will be a significant obstacle to effective treatment in the future.…”
Section: Discussionmentioning
confidence: 73%